Totally Extraperitoneal Approach With Preperitoneal Repair for the Treatment of Midline Hernia Defects: A Case Series and Single-Center Experience - Aritz Equisoain-Azcona; Javier García-Quijada García; Ramón Sanz-Ongil; Carlos Bustamante-Recuenco; Lucía Martínez-Minuesa; Álvaro Sobrino-Grande; Agustín Bertomeu-García; Francisco Javier Angulo-Morales (Journal of Abdominal Wall Surgery)
IntroductionThe introduction of laparoendoscopic techniques in abdominal wall surgery has transformed this field, growing exponentially in the last decade. The totally endoscopic preperitoneal approach (PeTEP) may offer advantages over traditional techniques by allowing complete anatomical restoration with lower morbidity. In order to evaluate the efficacy and safety of this novel technique, we reviewed our results 1 year after its implementation.Material and methodsWe perform a retrospective observational study including all patients aged over 18 years with midline hernias <8 cm with or without associated rectus diastasis who underwent PeTEP repair between March and December 2024 in our center. The evaluated outcomes included demographic characteristics, operative time, mesh size, length of hospital stay and morbimortality and recurrence rate.ResultsSeventeen patients (10♂, 7♀) were included, with a mean age of 49.82 years (SD: 12.43). Multiple defects were observed in 88.2% of cases, with the M2-M3 combination being the most frequent (41.2%). The mean defect diameter was 2.88 cm (±1.62). The superior access was the most frequent (66.7%), and a mesh with a mean height of 29.71 cm and a mean width of 14.41 cm was used. No conversions to open surgery were recorded, although three cases (17.6%) required a change to the retromuscular plane (eTEP-RS), being all of them female patients. Complications were limited to two superficial hematomas (11.8%). The median hospital stay was 1 day. With a median follow-up of 87 days (IQR 143.5), no recurrences were detected.ConclusionOur results suggest that the PeTEP approach is a safe and effective technique for small to medium-sized hernias with or without rectus diastasis. Additional studies with long-term follow-up and comparisons with pre-existing techniques are needed to confirm its benefits and establish its indications.